Factors associated with initiation of antiretroviral therapy among HIV-positive people who use injection drugs in a Canadian setting. (27th March 2016) - Joseph, Brenden; Wood, Evan; Hayashi, Kanna; Kerr, Thomas; Barrios, Rolando; Parashar, Surita; Richardson, Lindsey; Dobrer, Sabina; Guillemi, Silvia; Montaner, Julio; Milloy, M.-J.
Abstract : Objective: To identify behavioral, social, and structural factors associated with time from HIV seroconversion to antiretroviral therapy (ART) initiation among people who use injection drugs (PWID). Design: Two complementary prospective cohorts of PWID linked to comprehensive ART dispensation records in a setting of universal no-cost HIV/AIDS treatment and care. Methods: Multivariable extended Cox models of time to ART initiation among baseline HIV-seronegative PWID who seroconverted after recruitment adjusted with a time-updated measure of clinical eligibility for ART. Results: We included 133 individuals of whom 98 (74%) initiated ART during follow-up at a rate of 12.4 per 100 person-years. In a multivariable model adjusted for ART eligibility, methadone maintenance therapy [adjusted hazard ratio (AHR) = 2.37, 95% confidence interval (95% CI): 1.56–3.60] and a more recent calendar year of observation (AHR = 1.06, 95% CI: 1.00–1.12) were associated with more rapid ART initiation, whereas informal income generation (AHR = 0.51, 95% CI: 0.32–0.79) and incarceration (AHR = 0.52, 95% CI: 0.28–0.97) were negatively associated with ART initiation. Conclusion: In this sample of community-recruited HIV-positive PWID with well defined dates of HIV seroconversion, we found that two measures related to the criminalization of illicit drug use each independently delayed ART initiation regardless of clinical eligibility. Engagement in methadone promoted ART initiation. Programs to scale-up HIV treatment among PWID should consider decreased criminalization of PWID and increased access to opioid substitution therapy to optimize the impact of ART on HIV/AIDS-associated morbidity, mortality, and HIV transmission.